JUDICIAL MAFIA AND ITS PROBLEMS: AN EXAMINATION FROM THE INTERPRETATION OF IBN KATHĪR ON SURAH AL-MĀIDAH VERSE 8 AND AL-BAQARAH - Moh. Abdulloh Hilmi; Herfin Fahri (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2023)
This article discusses the judicial mafia within the religious and governmental landscape of Indonesia. The judicial mafia has recently come under scrutiny due to various issues of misconduct such as corruption, collusion, and nepotism. When examined further, the Quran also emphasizes that unfair and dishonest actions are intolerable, and in the legal perspective of Indonesia, it regulates criminal acts of corruption and their penalties. Using a descriptive-analytical method, the researcher will elucidate the principles of justice found in the Quran, specifically in Surah al-Mâidah [5]: 8 and Surah al-Baqarah [2]: 188, as interpreted by Ibn Kathȋr, and their relevance to Indonesian laws and government regulations. The findings of this study are as follows: First, Ibn Kathir asserts that achieving justice necessitates the presence of fair and faithful witnesses. Second, when a decision is made that is unjust and has detrimental effects on a case, it should be reconsidered by the judge for fairness. Third, the judicial mafia can be prevented through continuous monitoring and evaluation of institutional bodies.